Analisis Perbandingan Implementasi Protokol Routing Dinamis Open Shortest Path First (OSPF) dan Border Gateway Protocol (BGP) pada Lab Komputer Menggunakan Cisco Packet Tracer - Alim Hardiansyah; Mohammad Hilman; Holilah Holilah (Teknik Informatika Fakultas Ilmu Komputer, 2025)
Abstract Computer networks in the current era of globalization have developed very rapidly and are increasingly used by agencies around the world, which require effective routing protocols. One network that is often used is the internet, which has dynamic routing protocols such as Open Shortest Path First (OSPF) and Border Gateway Protocol (BGP). In this study, researchers conducted a network topology simulation design in sending data packets using OSPF and BGP. The purpose of this research is to analyze the performance comparison of the two dynamic protocols in a computer network simulation using Cisco Packet Tracer. The analysis results show that OSPF excels with low delay (12 ms), stable jitter (13.5 ms), and moderate throughput (25.58kbps), making it more suitable for real-time applications, while BGP shows better reliability with low packet loss (8.3%). Keywords: Routing, OSPF, BGP, Computer Network, Cisco Packet Tracer